(untitled) (Journal of the College of Basic Education, 2022)
The objective of the current research is to identify the effect of the proposed educational design based on the modified M.U.R.D.E.R strategy for memory aids in the achievement of mathematics among fourth-grade female students. In order to achieve the goal of the research, the experimental research method was adopted, and the real experimental design with two equal groups with a post-test was used to measure achievement, and the following zero hypothesis was put